Comparison of experimental data with model piles in normal and winter temperature conditions (0ºС, -5ºС) - Mineev, Нурсултан (Рroblems of engineering and professional education, 2023)
This article describes static testing of model piles in normal and seasonally freezing soil. Static tests of model piles were conducted in the laboratory of Karaganda State Industrial University (Temirtau, Kazakhstan). The test results determined the behavior of the model piles and their bearing capacity. The results of the tests are presented in graphical and tabular form.